Militarism and security: Dialogue, possibilities and limits. (February 2018) - Stavrianakis, Anna; Stern, Maria
While attention to security has grown exponentially over the last few decades, militarism – the preparation for and normalization and legitimation of war – has not received the widespread and sustained focus it warrants in mainstream or critical circles. Rather than stake a claim for one concept over the other, however, this article – and the special issue to which it serves as an introduction – asks how we are to understand the relationship between security and militarism, both as analytical tools and as objects of analysis. We examine, first, what analytical and political work militarism and security do as concepts, and how they can be mobilized methodologically; second, what the possibilities are of fruitful exchange between knowledges produced about these concepts or practices; and, third, what the limits are of militarism and security. In the process, we address the shifts in the world that international relations and its related subfields study; shifts in the institutional framing and materiality of fields and subfields of research; and shifts in how international relations studies the world. Read together, the contributions to the special issue make the case for a reinvigorated focus on the mutual co-constitution of militarism and security.